Astrocyte Physiology and Pathology - Teresa Gentile, Maria; Colucci D'Amato, Luca (IntechOpen, 2018)
A team of authors from prestigious academic schools contributed to draw up a project that would give a detailed account of astrocyte's morphology and physiology, examining thoroughly all the astrocyte's types; giving an accurate description of their morphology, location, function in the brain; and illustrating their physiology and pathology in terms of dealing with neurons through "gliotransmitters," ionic channels, and membrane receptors expression. This book gives an overview of the crucial role of astrocytes in the physiology of the CNS and in the pathogenesis of several CNS disorders suggesting that the shift from a neurocentric view to one that incorporates astrocytes in disease models for drug discovery is a critical step in renewing drug development strategies to treat neurodegenerative diseases.